Insight into electronic structure and optical properties of ZnTPP thin films for energy conversion applications: Experimental and computational study. (August 2022) - AlSaidi, Ramadhan A.M.; Alamri, Hatem R.; Sharma, Kamal; Al-Muntaser, A.A.
Abstract: Theoretical and experimental study of the electronic structure and optical characteristics of Zinc (II) 5, 10, 15, 20-tetraphenyl 21 H, 23 H-porphine (ZnTPP) was reported. The ground state molecular geometry, Frontier molecular orbitals, vibrational frequency, and total energy of ZnTPP were determined using density functional theory (DFT) calculations. Homogenous ZnTPP thin films were grown on glass and fused quartz substrates using the thermal evaporation method. The ZnTPP thin film structure was described experimentally using FTIR, XRD, AFM and UV-Vis. spectroscopy. XRD results illustrate the polycrystalline structure of ZnTPP powder, whereas the pristine ZnTPP thin films have amorphous nature. The AFM results revealed that the pristine ZnTPP film has uniform elliptical crystallites dispersed throughout the whole surface. Optical parameters of the ZnTPP films were obtained from the absorbance spectra. The absorption coefficient and band gap values showed that ZnTPP can be employed in optoelectronic devices. The experimental findings are in good accord with theoretical ones. A hybrid solar cell was prepared by growing a thin film of ZnTPP on p-silicon single crystal wafers. The photovoltaic performance of the prepared solar cell were estimated as JSC = 1.556 mA/cm 2, VOC = 0.366 V, FF = 0.274 and η = 3.12 %. Graphical Abstract: Molecular structure of ZnTPP. The plot of the absorption coefficient and d ( α ) / d ( h ν ) versus h ν . ga1